Pengaruh Kinerja Lingkungan dan Kinerja Keuangan terhadap Pengungkapan Lingkungan - Paramita Nurul Astrini; Lulus Kurniasih (Jurnal Akuntansi dan Bisnis, 2014)
This research is aimed to investigate the effect of environmental performance and financial performance on environmental disclosure on manufacturing companies listed in Indonesia Stock Exchange. Environmental performance is measured by using rating Environmental Performance Rating Program (PROPER), financial performance is measured by the profitability of the Net Profit Margin (NPM). Environmental disclosure is measured by a checklist on the disclosures performed by the company in the annual report. This research used a control variable is growth (growth company) and leverage. This research used sample of 48 manufacturing companies. The result showed that environmental performance has positive effect and significantly on environmental disclosure. Financial performance has no effect on environmental disclosure. This research has limitation that a minimum of samples used for environmental performance variables were measured using PROPER only in 2011.